The effect of preferred music versus disliked music on pain thresholds in healthy volunteers. An observational study - Timmerman, Hans; van Boekel, Regina L. M.; van de Linde, Ludo S.; Bronkhorst, Ewald M.; Vissers, Kris C. P.; van der Wal, Selina E. I.; Steegers, Monique A. H. (PLOS ONE, 2023)
Pain is a prevalent and debilitating healthcare problem. Since pharmacological treatments have numerous side-effects, additional treatment could be beneficial. Music has been shown to affect the pain perception and the pain threshold. The objective of this observational study was to evaluate the effect of preferred music as opposed to disliked music on pain (tolerance) thresholds and perceived pain intensity in healthy volunteers. Pain thresholds were measured via quantitative sensory testing. The volunteers were randomly assigned to either handheld pressure algometry to assess the pressure pain threshold to or electrical measurements to assess the electrical pain tolerance threshold while listening to preferred and disliked music. The pain thresholds were administered on the dorsal side of the forearm. The perceived pain intensity was assessed via a numerical rating scale, ranging from 0 (no pain) to 10 (worst pain imaginable). In total 415 volunteers were included in this study. The pressure pain threshold was assessed in 277 volunteers and in the electrical pain tolerance threshold test 138 volunteers were entered. In both groups, preferred music yielded higher pain thresholds than disliked music (P<0.001) and lower perceived pain intensity during the stimulus (P = 0.003). Moreover, the highest pain thresholds of both pressure pain and electrical pain tolerance thresholds were obtained when the preferred music was preceded by disliked music. Listening to preferred music when receiving noxious stimuli leads to higher pain thresholds and lower perceived pain scores in comparison with disliked music. Preferred music could be beneficial for patients with pain or undergoing painful procedures.